2008
DOI: 10.1029/2007ja012858
|View full text |Cite
|
Sign up to set email alerts
|

Polar mesospheric clouds: Infrared measurements from the Midcourse Space Experiment

Abstract: [1] Spatial Infrared Imaging Telescope (SPIRIT) III radiometer on the Midcourse Space Experiment (MSX) satellite measured highly structured infrared, IR, emission from polar mesospheric cloud (PMC) ice particles at northern latitudes above 51 degrees on 22 July 1996 in the 11.1 to 13.2 and 18.2 to 25.1 mm radiometer channels, bands C and E, respectively. Measurements of the PMC thermal emissions included the observation of an extended cloud at 84.8°N and 325.6°E at 0313:25 UT, a local solar time of approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…The spectral distribution of radiances measured by MIPAS in the 770–930 cm −1 region is very similar to that simulated for ice particle emission at low temperatures (below 150 K). This provides further evidence (after that of Hervig et al [2001], Eremenko et al [2005], Grossmann et al [2006] and O'Neil et al [2008]) of the water ice nature of the PMC particles. As a further check, the regions where MIPAS detected PMCs were compared to those derived from SCIAMACHY data and it was found that they coincide very well, although the percentage of scans with PMCs in the 60°N–90°N region is larger in SCIAMACHY than in MIPAS, probably because of the better sensitivity of SCIAMACHY (measuring in the UV) compared to MIPAS (observing in the infrared).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The spectral distribution of radiances measured by MIPAS in the 770–930 cm −1 region is very similar to that simulated for ice particle emission at low temperatures (below 150 K). This provides further evidence (after that of Hervig et al [2001], Eremenko et al [2005], Grossmann et al [2006] and O'Neil et al [2008]) of the water ice nature of the PMC particles. As a further check, the regions where MIPAS detected PMCs were compared to those derived from SCIAMACHY data and it was found that they coincide very well, although the percentage of scans with PMCs in the 60°N–90°N region is larger in SCIAMACHY than in MIPAS, probably because of the better sensitivity of SCIAMACHY (measuring in the UV) compared to MIPAS (observing in the infrared).…”
Section: Discussionsupporting
confidence: 63%
“…The spectral shape of the simulated signal closely resembles the MIPAS coadded spectrally degraded PMC spectra (Figure 2). This provides further evidence (after that of Hervig et al [2001], Eremenko et al [2005], Grossmann et al [2006] and O'Neil et al [2008]) of the water ice nature of the PMC particles.…”
Section: Pmc Infrared Spectrasupporting
confidence: 63%
See 1 more Smart Citation
“…While the lidar signal varies with r 6 , the MIPAS (in IR emission) and SOFIE (in IR extinction) signals change with the total ice volume density. As the ice particle size decreases towards higher altitudes (Baumgarten and Fiedler, 2008;Hervig et al, 2009b;Pérot et al, 2010), MIPAS and SOFIE are then more sensitive than lidars to clouds at higher altitudes. The highest altitude of PMCs derived from MIPAS NLC mode measurements is largely variable, as can be seen in the typical examples shown in Fig.…”
Section: Top Altitudementioning
confidence: 99%
“…(e.g. Baumgarten and Fiedler, 2008;Fiedler et al, 2009;Gumbel and Witt, 1998;Bailey et al, 2005;DeLand et al, 2003;Petelina et al, 2006;von Savigny et al, 2005von Savigny et al, , 2007von Savigny and Burrows, 2007;Pérot et al, 2010;Russell III et al, 2009); as well as sophisticated models (e.g. Berger and Zahn, 2002;Berger and von Zahn, 2007).…”
Section: Introductionmentioning
confidence: 99%